Mobile Learning: Implementation on Mathematics Learning - sari herlina; Endang Istikomah (UIR PRESS, 2018)
The Development of technology that is increasingly advanced encourages the creation of innovation in learning. These forms of innovation that like learning media, one of that is mobile learning aplication. This aplication can used as a support in the learning procces. In this research aims to show at respon of students on used mobile learning aplication in mathematics learning on material of calculus II in mathematics education departement FKIP Islamic University of Riau. Forms of this research is descriptive research that doing on even semester on learning year 2017/2018. Instrument of this research is questionnaire sheet, with data collection technique used sheet of respon use mobile learning aplication. Analysis of data in this research was carried out by analysis descriptive of questionnaire given. Result of this research showed good respon because based of result of questionaire given obtained 75,10% give positive respon. This mobile learning aplication still needs more development based respon given of students.